2018
DOI: 10.1002/etep.2713
|View full text |Cite
|
Sign up to set email alerts
|

A novel low-voltage ride-through capable energy management scheme for a grid-connected hybrid photovoltaic-fuel cell power source

Abstract: Summary A novel low‐voltage ride‐through capable energy management control system is proposed for a grid‐connected hybrid photovoltaic‐fuel cell power source. The scheme is designed to enable the hybrid power source to follow a power demand from the grid operator. Additionally, the system is able to ride through both symmetrical and asymmetrical voltage sags while providing active and reactive power support to the grid. The injected active power is kept constant during asymmetrical voltage sags without requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This system can meet the power demand of a hybrid power supply following the power grid operation post. The simulation results show that this method can reduce the computational complexity of the control system and is highly effective in managing energy under normal and voltage sag conditions [8].…”
Section: Related Workmentioning
confidence: 96%
See 1 more Smart Citation
“…This system can meet the power demand of a hybrid power supply following the power grid operation post. The simulation results show that this method can reduce the computational complexity of the control system and is highly effective in managing energy under normal and voltage sag conditions [8].…”
Section: Related Workmentioning
confidence: 96%
“…In formula (8), y is used to describe the device state signal after denoising; i represents the number of basic mode components; i e is used to describe the basic mode components after threshold processing; n represents the length of the basic mode component. By combining signal reconstruction, a noise-free operating state signal of power equipment can be obtained [20][21].…”
Section: Pemfc Operation Smo In View Of Dt Modelmentioning
confidence: 99%
“…The study concluded that this method is expensive. A study is carried out on the technical feasibility of PV-based off-grid system with battery and hydrogen storage system [15]. In the same way, the technical feasibility of hybrid solar PV/hydrogen fuel cell is examined [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The PWM signal output is obtained through digital pin 4 of the Arduino Board. The control algorithm is downloaded to Arduino board from the MATLAB Simulink support package 25 …”
Section: Experimental Verification Of Proposed Pem Fuel Cell Emulatormentioning
confidence: 99%